Biodiversity inventory of the Protected Area for the Management of Habitats or Species of Matela (Terceira, Azores, Portugal). Version 1.1. - Sousa, Mariana (2024)
The data presented in this study comprises a collection of observations documented within the frame of the LIFE IP Azores Natura project (2019-2027) in the Azores archipelago. The primary goal of this project is to implement conservation measures on both land and sea, with the aim of enhancing the conservation status of species and habitats covered by the Birds and Habitats Directives. For the documentation of flora occurrences in the project's intervention areas, the QField application was employed. This application not only facilitated the recording of the locations where various flora species were encountered but also allowed field workers to capture additional details, including the surrounding habitat, abundance, developmental stage, phenological state, identified threats, observer identity, and the observation date. Through this publication, we contribute valuable information about the distribution of flora species in the Azores. As of now, a total of 1929 observations have been recorded, encompassing both exotic and native species.